Korelasi Hamba Tuhan Yang Dipenuhi Roh Kudus Dengan Perintisan Gereja - Parhusip, Mangatas; Ginting, Erwanda; Boiko Gulo; Melki Siregar; Manurung, Yohana Sapna (Universitas Methodist Indonesia, 2025)
Church planting represents a central dimension of the church’s mission, particularly within the Indonesian Methodist Church. This study investigates the correlation between Spirit-filled servants of God and the success of church planting in District 3, Region I. A quantitative research design was employed, in which data were collected through questionnaires distributed to 140 respondents. The responses were analyzed using correlation analysis to examine the relationship between the empowerment of the Holy Spirit and the effectiveness of pioneering new congregations. The findings reveal that the Holy Spirit plays a decisive role in the church planting process. Servants of God who are filled with the Holy Spirit demonstrate greater resilience, vision, and spiritual authority, all of which significantly enhance their capacity to establish new churches. The study concludes that spiritual empowerment is not merely supportive but essential in ensuring the effectiveness of church planting efforts. Moreover, the results suggest that pastoral leadership rooted in the Holy Spirit provides both theological and practical strength for overcoming challenges in mission fields. This research underscores the importance of integrating spiritual formation with practical ministry strategies, offering valuable insights for church leaders and theological institutions in fostering sustainable growth. Keywords: Holy Spirit, pastoral ministry, church planting, correlation